Kepastian Hukum Jumlah Modal Dasar Pendirian Perseroan Terbatas Setelah Berlakunya PP Perubahan Modal Dasar Perseroan Terbatas - Pratama, Ida Bagus Putra; Priyanto, I Made Dedy (Acta Comitas; Vol 5 No 2 (2020)DO - 10.24843/AC.2020.v05.i02.p11, 2020)
Research on legal certainty the amount of basic capital establishment of limited liability company based on the norms of conflict between article 32 paragraph (1) of the limted liability company law concerning "the limited liability company capital of at least Rp 50,000,000.00" with article 1 paragraph (3) of government regulations The limited liability of the company's capital of limited liability concerning "the founding capital of the company is determined by agreement”. 2 problem are formulated: (1) What is the form for deposit of stock capital on the provisions of article 33 of the limited liability company law, (2) How is the legal certainty of the number of basic capital of the limited liability After the validity of government regulation change of the limited liability company. This purpose research is finding form of the deposit of stock capital and the basic capital of the limited liability company before and after enforcement of government regulation of limited liability of the company. The legal research method used normative legal research method with statute approach and conceptual approach. Capital deposits of shares can be made in the form of money and other forms of immovable tangible objects such as land and intangible objects in the form of bill of Rights; and arrangements regarding the underlying capital applicable in the establishment of the limited liability company is Article 1 paragraph (3) of government regulation of the limited liability of the company.